Carlos Alberto Moreyra, Esoterismo religioso del Siglo de Oro español. Ed. del Autor, Córdoba (Argentina), 1965; 72 pp. - Soons, Alan (El Colegio de México, 1970)
Se reseñó el libro: Esoterismo religioso del Siglo de Oro español.